O‘ZBEKISTON RESPUBLIKASINING OROL DENGIZI EKOLOGIK MUAMMOSI YUZASIDAN BMT BILAN HAMKORLIGI - Abatov, A.R. (SCIENCE and SOCIETY, 2024)
This article will focus on Uzbekistan's cooperation with international organizations in solving acute problems facing the residents of the Aral Sea region. The United Nations is a key partner in addressing the problems caused by the drying up of the Aral Sea.
Keywords: Aral Sea disaster; ecology; environment; international organizations; UN; nature; factor; fruits of cooperation